Impregnation of cinnamon essential oil into plasticised polylactic acid biocomposite film for active food packaging - Anuar, Hazleen; Abu Bakar, Nur Fatin Izzati; Syed Mustafa, Sharifah Nurul Inani; Mohd Apandi, Siti Nur E’zzati; Abd Rashid, Siti Munirah Salimah; Ali, Fathilah; Manshir, Mohd. Romainor (Springer International Publishing AG., 2017)
The investigation of environmentally friendly and sustainable food packaging for daily high consumption is necessary to replace existing synthetic packaging. This study reported the efects of antimicrobial agents on the properties of durian skin fbre (DSF)-reinforced plasticised polylactic acid (PLA) biocomposite flms produced via solvent casting. Cinnamon essential oil (CEO) was incorporated into the PLA biocomposite at amounts from 0 to 5 wt%. Thermogravimetric analysis showed the lowest weight loss due to biocomposite degradation after 500 °C in 1 wt% CEO flm. Diferential scanning calorimetry analysis showed that the biocomposites with CEO were less crystalline suggesting that the structure of the biocomposite was less rigid and fexible. CEO improved the barrier properties of the biocomposite by decreasing the water vapour permeability. Biocomposites with CEO also demonstrated antimicrobial activity against both gram-positive and gram-negative bacteria. The plasticised PLA/DSF biocomposite with CEO is transparent, indicating potential as an active food packaging material.